Perancangan Christian Community Center dengan Pendekatan Arsitektur Neo-Vernakular di Kupang, Nusa Tenggara Timur - Yolanda Magdalena Hobamatan; Putri Suryandari; Karya Subagya (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2020)
Indonesia is one of country that has ethnic, racial, cultural and religious diversity. Kupang city is the capital city of East Nusa Tenggara, is one of the regions in Indonesia with a Christian majority population. Christian Community Center expected to be able to be a place that can be accommodate various church denominations in one of spiritual activities and social with facilities that can accommodate, and can be a place to training for anyone who has the desire to develop talents to serve God and Christian Community Center can be a new icon for Kupang City. The concept of neo-vernacular architecture can be able to revive some cultural elements of East Nusa Tenggara through the trend of rehabilitation or renewal and reuse of philosophical and cosmological forms and values of an area but in the form of a new and modern design.